Citizenship without states: rehabilitating citizenship discourse among the anarchist left. Issue 5 (4th July 2019) - Smith, Brian
ABSTRACT: The purpose of this paper is threefold. First, it seeks to give expression to the trends of an important debate that has not been formally articulated among anarchist theorists, namely whether or not the concept 'citizenship' can be meaningfully salvaged and repurposed. While many anarchist theorists have gestured at such a debate, the dimensions of this discourse have not been clarified. Secondly, in identifying the features of this debate, this paper seeks to show that citizenship can be meaningfully rehabilitated by the anarchist left. And finally, this essay seeks to provide some preliminary reasons why anarchist theories of citizenship may provide a fruitful partnership with theorists of citizenship today, especially those engaging in critical citizenship studies.